Problems identified and experienced by some student teachers in student teaching - Olaso, Ignacia B. 1912- (Quezon City, Philippines College of Education, University of the Philippines Diliman, 1966)
This study determines the nature and scope of the problems or situations which student teachers consider as a source of concern and the extent to which these problems or situations exist among a sampling of student teachers.
Thesis (Master of Education)--University of the Philippines Diliman; 1966
Keywords: Student teaching -- Case studies